A Systematic Review on Talent Management and Retention Practices - Panday, Priyanka; Kaur, Gagandeep (International Journal of Psychosocial Rehabilitation, 2020)
The world is moving toward the highly competitive environment. The talent management has been catching the attention of practitioners and professionals these days. Though, abundant literature is available to synthesize the existing knowledge about the talent management and retention issues. The aim of this paper is to consolidate the existing findings about the relationship between talent management and retention and present it systematically. We have adapted the method given by Lage junior et al. (2010); Jabbour (2013); Seuring (2013), and analyzed the articles published between 2011 and 2017 from the web of sciences database. The results indicates that research is growing positively towards creating a new perspective and adding new dimensions to the study, More empirical studies are required in order to test the conceptual and new models. The findings further reveled that greater focus on manufacturing industries; developed countries and research using quantitative studies are required in order to fill the existing gap in literature in talent management and retention related studies to test the conceptual work and new concepts.